Determinants and constraints to effective procurement management in government projects: a practitioner's perspective - Ahmed, Jalal Uddin (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.